Analisis Akuntansi Lingkungan di Rumah Sakit Umum SK Lerik Kota Kupang - Helda Marlin Ala; Mesri W.N. Manafe (Jurnal Inovasi Kebijakan, 2021)
This study aims to test environmental accounting at the SK Lerik General Hospital, Kupang City. Data analysis uses quantitative descriptive analysis. The test uses quantitative and qualitative descriptive analysis by comparing research results with relevant theories. The City of Kupang has produced waste at the source as the first effort has been carried out using an WWTP machine to prevent or reduce the occurrence of waste that comes out of hospital operational activities. Waste has been managed properly and has carried out accounting treatment stages for waste management costs, which include costs for liquid waste, solid waste, costs for water, fuel, electricity, room and building sanitation, air quality monitoring, insect control, equipment depreciation and WWTP operating costs.